Estimation of Stature from Foot Length Measurements in Students of a Medical College of Kathmandu: A Cross-sectional Study (Nepal Medical College Journal, 2025)
Identification refers to the determination of individuality of a person based on certain physical characteristics. It has been proved by researchers that a strong co-relation exists between one’s stature and footprint/ foot outline measurements. Estimation of stature forms a basic domain during the investigation of unknown/ comingled human remains. The dimensions measured in the lower extremities of the body have greater association with the stature of the individual than those from the upper extremities. This study was conducted from May 2024 to October 2024 AD in 153 medical students of Nepal Medical College, Kathmandu. The height of each person of the study was measured using height scale and right and left foot length was measured using vernier calipers. Linear regression formula (a+bx) for estimating the stature of male and females and of total subjects, was obtained from the data entered in SPSS version 16. Based on the data, the mean height of males was 170.41 ± 6.12, that of females was 158.28 ± 6.21. The right and left foot length of males was 24.41 ± 1.24 and 24.64 ± 1.26 and for females was 22.36 ± 1.17 and 22.39 ± 1.19 respectively. Significant associationwas obtained between the height and foot lengths of males and females of the study.Regression formulae were obtained from the respective heights and foot lengths of total sample, males and females which showed significant co-relation (P